UPAYA PENCEGAHAN STUNTING DI DESA BANJAR NEGERI: TANTANGAN DAN SOLUSI - RUKMANSYAH, DEA FIBRIANI; SUSANTI, AGUS; L, LENTARIWIDYA; S, CITRA PEMATA; APRILIANI, USSY (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to provide knowledge to the Banjar Negeri Village women's group. This activity was attended by 35 mothers with toddlers. The method used is an oral presentation using PPT (Powerful Presentation Techniques) media, discussion and questions and answers. According to the general guidelines for balanced nutrition (PUGS), the arrangement of dishes must be present and must consist of rice, side dishes, vegetables and fruit which include staple foods as energy sources, side dishes as sources of protein and fat, vegetables and fruit as mineral sources and vitamin. Fruit and vegetables are food sources that are rich in vitamins and minerals which are very beneficial for the health, development and growth of our bodies. The prevalence of malnutrition cases in the Banjar Negeri village is around 5 children out of 213 children. The aim of this service is to form a group of mothers who are alert to stunting and increase mothers' knowledge about the meaning of stunting, the impact and ways to prevent stunting and malnutrition with the fill my plate program. ABSTRAKKegiatan pengabdian masyarakat ini bertujuan untuk memberikan pengetahuan pada kelompok ibu Desa Banjar Negeri. Kegiatan ini diikuti 35 ibu-ibu yang mempunyai balita. Metode yang dilakukan adalah presentasi oral dengan menggunakan media PPT (Powerfull Presentation Techniques) diskusi dan tanyajawab. Menurut panduan umum gizi seimbang (PUGS) susunan hidangan harus ada dan wajib terdiri dari nasi, lauk, sayur serta buah-buahan yang meliputi makanan pokok sebagai unsur sumber energi, lauk sebagai unsur sumber protein dan lemak, sayuran dan buah sebagai unsur sumber mineral dan vitamin. Buah dan sayur merupakan unsur sumber pangan yang kaya akan vitamin dan mineral yang sangat bermanfaat untuk kesehatan, perkembangan, dan pertumbuhan tubuh kita. Prevalansi kasus gizi buruk di desa banjar negeri ada sekitar 5 anak dari 213 anak. Tujuan dari pengabdian ini adalah pembentukan kelompok ibu siaga stunting dan meningkatkan pengetahuan ibu tentang pengertian stnting, dampak dan cara pencegahan stunting dan gizi buruk dengan program isi piringku.